Hyperuricemia Prevalence and Its Metabolic Syndrome Profiles - Stefanie Yuliana Usman; Guntur Darmawan; Laniyati Hamijoyo; Rachmat Gunadi Wachjudi (Indonesian Journal of Rheumatology, 2019)
Background: The prevalence of hyperuricemia has increased overtime globally. Moreover, it has been linked with several metabolic syndromes. A study in Depok City and Denpasar showed prevalence of hyperuricemia were up to 18.6% and 18.2%, respectively. Urban lifestyle has been proposed to contribute for hyperuricemia; however, there is no published study conducted in rural population yet. Therefore, we performed this study to evaluate the prevalence and metabolic syndromes profile of hyperuricemic patients in rural area. Methods: A cross sectional study was conducted at regional government hospital in North Kayong Regency, West Kalimantan. We retrieved all complete internal medicine outpatient data between October and December 2018. All non-pregnant, adult patients newly diagnosed with hyperuricemia or currently taking uric acid lowering drug were included in this study. Result: A total of 44 out of 121 subjects (36.36%) had hyperuricemia; 25 subjects (56.81%) were male and had median age of 53 years old. Mean level of serum uric acid was 8.30Â±1.77mg/dl. The metabolic syndrome profiles (diabetes mellitus, obesity, hypertension, hypercholesterolemia and hypertriglyceridemia) vary among subjects; ranging from 20.45% (hypertriglyceridemia) to 86.36% (hypertension). Conclusion: Hyperuricemia and its metabolic disorders are an emerging burden of disease in rural area in Indonesia.